Increased risk of type 2 diabetes after traumatic amputation: a nationwide retrospective cohort study - Yoo, Jung Eun; Lee, Dagyeong; Kim, Bongseong; Chang, Won Hyuk; Jin, Sang-Man; Han, Kyungdo; Shin, Dong Wook (Frontiers in Endocrinology, 2025)
BackgroundAmputation confers disabilities upon patients and is linked to cardiometabolic morbidity and mortality. We aimed to compare the incidence of type 2 diabetes (T2DM) between individuals following amputation with those of the general population.MethodsWe performed a population-based retrospective cohort study using the Nationwide Health Insurance Service database. A total of 21,343 individuals with amputation during 2010–2018 and their 1:3 age- and sex-matched controls was included. We conducted Cox proportional hazard analysis to calculate the risk of T2DM among individuals with amputation.ResultsDuring the 4.2 ± 2.5 year mean follow-up period, there were 912 incident T2DM cases (10.7 per 1,000 person-years) among individuals with amputation. Individuals with amputation had a higher risk for T2DM (adjusted hazard ratio [aHR] 1.11, 95% confidence interval [CI] 1.03–1.20) compared with matched controls. The risks were increased further when accompanied with disability; those with severe disability had a higher risk of T2DM (aHR 1.77, 95% CI 1.20–2.60) than matched controls. Individuals with proximal upper limb amputation (aHR 1.10, 95% CI 1.02–1.18) and proximal lower limb amputation (aHR 3.60, 95% CI 1.50–8.64) had a higher risk of T2DM compared with matched controls.ConclusionsIndividuals with amputation were at significantly greater risk for T2DM than the general population, particularly those with severe disability and proximal amputation. Innovative strategies that improve and support the long-term T2DM risk for severely injured individuals with proximal amputation are warranted.